Improving perioperative pain management: a preintervention and postintervention study in 7 developing countries. (January 2019) - Zaslansky, Ruth; Chapman, C. Richard; Baumbach, Philipp; Bytyqi, Adem; Castro Lopes, José M.; Chetty, Sean; Kopf, Andreas; Li, Li; Ern Ming, Lim; Olawoye, Olayinka; Rizza Parico, Jane; Soyannwo, Olaitan; et al.
Abstract: Introduction: The burden of untreated postoperative pain is high. Objective: This study assessed feasibility of using quality improvement (QI) tools to improve management of perioperative pain in hospitals in multiple developing countries. Methods: The International Pain Registry and Developing Countries working groups, from the International Association for the Study of Pain (IASP), sponsored the project and PAIN OUT, a QI and research network, coordinated it, and provided the research tools. The IASP published a call about the project on its website. Principal investigators (PIs) were responsible for implementing a preintervention and postintervention study in 1 to 2 surgical wards in their hospitals, and they were free to choose the QI intervention. Trained surveyors used standardized and validated web-based tools for collecting findings about perioperative pain management and patient reported outcomes (PROs). Four processes and PROs, independent of surgery type, assessed effectiveness of the interventions. Results: Forty-three providers responded to the call; 13 applications were selected; and PIs from 8 hospitals, in 14 wards, in 7 countries, completed the study. Interventions focused on teaching providers about pain management. Processes improved in 35% and PROs in 37.5% of wards. Conclusions: The project proved useful on multiple levels. It offered PIs a framework and tools to perform QI work and findings to present to colleagues and administration. Management practices and PROs improved on some wards. Interpretation of change proved complex, site-dependent, and related to multiple factors. PAIN OUT gained experience coordinating a multicentre, international QI project. The IASP promoted research, education, and QI work. Abstract : Supplemental Digital Content is Available in the Text.